Legal and Policy Narratives and the Return of Class in American Tax Policy - Charlton, Guy; Skilling, P. (Creighton University * School of Law, 2014)
In the late 19th and early 20th centuries, tax politics were structured by a bitter class struggle. Much of this struggle revolved around the government's competence to ensure the appropriate liberty, equality of opportunity and fairness to individuals, and the use of governmental power to ameliorate social and economic problems. For much of the 20th century, however, income tax was framed in a "hegemonic logic" in which re-distributive concerns were subordinated to an assumption of the shared benefits of economic growth. This Article discusses the recent return of a class-based politics to income tax politics in the United States. Drawing on the problem definition and narrative analysis literature, it argues that despite the recent resurgence of class-based rhetoric and political action, it is unlikely that America will return to the redistributive zero-sum income tax policies advocated prior to the 1920s. The underlying premises of the historical American liberal state, as evidenced in early substantive due process decisions: liberty, equality, and a distrust of governmental authority, which suggest a continuous fear of governmental power being used to interfere with individual liberty, circumscribes the debate over tax policy and lessens its class basis.